Task-shifting to improve asthma education for Malawian children: a qualitative analysis - Lovemore Nkhalamba; Sarah Rylance; Adamson S. Muula; Kevin Mortimer; Felix Limbani (BMC, 2021)
Abstract Background Asthma education, a key component of long-term asthma management, is challenging in resource-limited settings with shortages of clinical staff. Task-shifting educational roles to lay (non-clinical) staff is a potential solution. We conducted a randomised controlled trial of an enhanced asthma care intervention for children in Malawi, which included reallocation of asthma education tasks to lay-educators. In this qualitative sub-study, we explored the experiences of asthmatic children, their families and lay-educators, to assess the acceptability, facilitators and barriers, and perceived value of the task-shifting asthma education intervention. Methods We conducted six focus group discussions, including 15 children and 28 carers, and individual interviews with four lay-educators and a senior nurse. Translated transcripts were coded independently by three researchers and key themes identified. Results Prior to the intervention, participants reported challenges in asthma care including the busy and sometimes hostile clinical environment, lack of access to information and the erratic supply of medication. The education sessions were well received: participants reported greater understanding of asthma and their treatment and confidence to manage symptoms. The lay-educators appreciated pre-intervention training, written guidelines, and access to clinical support. Low education levels among carers presented challenges, requiring an open, non-critical and individualised approach. Discussion Asthma education can be successfully delivered by lay-educators with adequate training, supervision and support, with benefits to the patients, their families and the community. Wider implementation could help address human resource shortages and support progress towards Universal Health Coverage. Trial registration The RCT was registered in the Pan African Clinical Trials Registry: PACTR201807211617031